"Golf ball liver": agent orange hepatitis. Issue 5 (May 1997) - Leonard, C; Burke, C M; O'Keane, C; Doyle, J S
Abstract : 2, 4-Dichlorophenoxyacetic acid (2, 4-D) is a selective weedkiller which works by uncoupling oxidative phosphorylation and is in widespread use. It is known as "agent orange". A 65 year old man had acute hepatitis, thought to be caused by exposure to 2, 4-D. The patient ingested 2, 4-D as a result of habitual licking of his golf ball. Clinical and histological data together with a challenge test confirmed the diagnosis of "golf ball liver".